ANALISIS HAK KEPEMILIKAN LAHAN PERKEBUNAN KELAPA SAWIT DI DESA SETABU DAN DESA LIANG BUNYU KECAMATAN SEBATIK BARAT KABUPATEN NUNUKAN - Deby Ayu Herlin; Adi Sutrisno (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2019)
ABSTRACT While the research objectives formulated based on the background are: (1) to know the ownership rights of plantation land based on legislation in laws in the Republic of Indonesia; (2) to know the facts of land ownership rights of oil palm plantations in Setabu Village and Liang Bunyu Village, West Sebatik District, Nunukan Regency; and (3) to know the suitability of the land ownership rights stated in the laws and regulations with the ownership facts in Setabu and Liang Bunyu Villages in West Sebatik District, Nunukan Regency. The data used consists of secondary data and primary data, collected using document study techniques and interviews using questionnaires. The data obtained are then analyzed using qualitative content analysis techniques and qualitative descriptive analysis. The results of this study are (1) plantation land ownership rights based on laws and regulations consisting of ownership rights, use rights, business use rights and customary rights, where ownership rights are the most fulfilled and strongest rights: (2) plantation land rights over land controlled by farmers in Setabu Village and Liang Bunyu Village are